Natural product compounds from Calophyllum depressinervosum - Zamakshshari, Nor Hisam; Ee, Gwendoline Cheng Lian; Teh, Soek Sin; Daud, Shaari; Karunakaran, Thiruventhan; Ismail, Intan Safinar (Universiti Putra Malaysia Press, 2016)
Our detailed study on the phytochemistry of the stem bark of Calophyllum depressinervosum resulted in the isolation of four xanthones and one coumarin. The xanthones are trapezifolixanthone (1), macluraxanthone (2), ananixanthone (3), caloxanthone C (4) and the coumarin calonolide E2 (5). The structures of these compounds were elucidated using spectroscopic analysis such as 1D and 2D-NMR, GCMS, IR and UV.